2002
DOI: 10.1103/physrevlett.88.157201
|View full text |Cite
|
Sign up to set email alerts
|

Individual Domain Wall Resistance in Submicron Ferromagnetic Structures

Abstract: The resistance generated by individual domain walls is measured in a FePd nanostructure. Combining transport and magnetic imaging measurements, the intrinsic domain wall resistance is quantified. It is found positive and of a magnitude consistent with that predicted by models based on spin scattering effects within the walls. This magnetoresistance at a nanometer scale allows a direct counting of the number of walls inside the nanostructure. The effect is then used to measure changes in the magnetic configurat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(57 citation statements)
references
References 15 publications
5
52
0
Order By: Relevance
“…Due to the simplicity of device geometry, it is an open question as to where the DW nucleation starts (possibly at the wire ends or at some local inhomogeneties within the wire) although they are eventually detected within the voltage probes. Similar jumps in the longitudinal resistance have been observed in FePd nanostructure [24]. Multiple vortex walls have also been observed in planar NiFe nanowire of larger width [15].…”
supporting
confidence: 75%
“…Due to the simplicity of device geometry, it is an open question as to where the DW nucleation starts (possibly at the wire ends or at some local inhomogeneties within the wire) although they are eventually detected within the voltage probes. Similar jumps in the longitudinal resistance have been observed in FePd nanostructure [24]. Multiple vortex walls have also been observed in planar NiFe nanowire of larger width [15].…”
supporting
confidence: 75%
“…A clever device structure fabricated from an epitaxial L1 0 FePd film was used to detect and count individual domain walls by Danneau et al [53] -made possible by the comparatively large DW resistance in this material [237,113,184]. A L-shaped wire was fabricated with the legs running parallel and perpendicular to the stripe domains created during sample growth, which lie along a preferred direction.…”
Section: Mesoscopic Devicesmentioning
confidence: 99%
“…[4][5][6][7][8][9] Interestingly, the DW resistance turned out in some cases to be negative, 5,6 whereas in other cases to be positive. 4,[7][8][9] Both results have found theoretical explanations.…”
Section: Introductionmentioning
confidence: 98%
“…[4][5][6][7][8][9] Interestingly, the DW resistance turned out in some cases to be negative, 5,6 whereas in other cases to be positive. 4,[7][8][9] Both results have found theoretical explanations. [10][11][12] Levy and Zhang 10 showed that diffuse scattering between electronic states of opposite spin orientation, which occurs in the process of electron transport across the rotating magnetization within a DW, leads to increased resistance.…”
Section: Introductionmentioning
confidence: 98%